Pengaruh Status Gizi Ibu Hamil Primigravida Trimester III Dengan Kejadian Perdarahan Ante Partum (Hap) Di Blud Rs Dr.H.Moch. Ansari Saleh Banjarmasin Tahun 2014 - Sugeng Riyanto; Ermas Estiyana; Lia Septiliana; STIKES Husada Borneo; Alumni STIKES Husada Borneo (HB PRESS, 2015)
Antepartum hemorrhage is bleeding in women after pregnancy at 28 weeks. Bleeding in the future have a higher risk of severe and dangerous than the bleeding before 28 weeks gestation. Pregnancy changes the mother's physical and mental in nature. Mom must have good health and have adequate nutrition before and after pregnancy. Maternal nutrition during conception must be in good condition and during the pregnancy the mother should get extra protein, iron, calcium, vitamins, folic acid and energy. Deficiency or excess food intake during pregnancy can be bad for the mother, fetus and on time delivery. The causes factors of maternal and fetal death due to lack of awareness for antenatal mothers, not helped in childbirth, malnutrition and others. This study aims to determine the effect of nutritional status of pregnant women with incident primigravida third trimester haemorrhage antepartum (HAP) in BLUD Hospital H. Moch Ansari Saleh Banjarmasin in 2014. Study using survey methods with cross sectional analytic. The study population was all pregnant women in the third trimester primigravida in delivery room BLUD H. Moch Ansari Saleh Banjarmasin. Based on the results of the chi square test, no effect of nutritional status of pregnant women in the third trimester primigravida incidence of haemorrhage antepartum (HAP) in the BLUD H. Moch Ansari Saleh Banjarmasin in 2014.